Pengelolaan Sampah Plastik Menjadi Ekobrik Untuk Mencegah Pencemaran Sampah Mikroplastik di Desa MekarAsih - Simatupang, Dwi Sartika; Febriansyah; Yuni Yulistianti (Jurnal Inovasi Pengabdian Masyarakat, 2025)
Plastic waste is a serious problem because it is very difficult to decompose naturally. Various studiesshow that there are a number of plastic concentrations in the bodies of aquatic organisms, such as plankton, shellfish, crustaceans, and fish. The concentration of plastic in the human body can trigger growth that threatens human health and survival. Many people's products use plastic wrap, so a lot of plastic waste is wasted every day. Therefore, to prevent the accumulation of plastic waste, we must try to reduce its bad impact. This service activity carries out proper waste management using the concept of partnership with the community. The research method in this journal is descriptive qualitative which is supported by the SWOT analysis method to formulate strategies according to research objectives based on the analysis method used shows that the comparison between strengths and weaknesses, where weaknesses are greater than strengths. With the results of this analysis, waste management strategies are implemented in the Mekarasih Village community by establishing cooperation with schools and the community. The purpose of this activity is to reduce and prevent plastic waste pollution in Mekarasih Village.